Musicalizando a dança : em busca de uma educação músico-corporal direcionada aos processos de criação e atuação em dança - PINHEIRO, Débora Cardoso (Universidade Federal do Pará, 2019)
Symphony MUSDAN mentions the initial title of this research, as are highlighted, and deals with the intention of doing musicalize dance in order to meet the musical needs of this area of knowledge, taking into account the experiences in the discipline "Music and Dance "of the Bachelor's Degree in Dance UFPA. It stands out as general objective: To investigate ways to design a teaching and learning from the study of body movement possibilities in search of a musician-body education directed to processes in dance. So, they were tested in laboratory ways of relating dance and music in one make, intertwining Movement Factors (LABAN, 1989) and Sound parameters (SCHAFER, 1991), so that some elements of music were understood through the movements of body, the dance itself. For this, the perspectives and principles of authors were applied as Klauss Vianna, Ciane Fernandes, who talk about body awareness and study of body movements; Fayga Ostrower, Lenora Lobo and Cassia Navas and Sonia Rangel, who talk about creating processes; Jaques- Dalcroze, Marisa Fonterrada, Teresa Bushman and Beatriz Ilari, who talk about pedagogies in music education; Maria Fux, Maria Mommensohn and Paul Petrella, who talk about the relationship between music and dance. In addition, Bakhtin is used as a means for you to do to understand the concept of established dialogue between the two arts. The survey found ways to appropriation by a music and dance through it, both for teachers and for students, dance artists and choreographers, so that they can consciously enjoy other possibilities of thinking their processes